Thermomigration in lead-free solder joints - Abdul Hamid, M. F (Inderscience Publishers, 2008)

(untitled)
In the next generation nanoelectronics and SiC based electronic packaging, current density and temperature gradient will be larger in orders of magnitude. Electromigration and thermomigration are considered to be major road blocks leading to realisation of nanoelectronics and SiC based high temperature power electronics. In this paper, damage mechanics of 95.5Sn4Ag0.5Cu (SAC405) lead-free solder joints under high temperature gradients have been studied. This paper presents observations on samples which were subjected to 1000Â°C/cm thermal gradient for two hours, 286 hours, 712 hours and 1156 hours. It was observed that samples subjected to thermal gradient did not develop a Cu3Sn intermetallic compound (IMC) layer at the hot side due to Cu migration to the cold side thus causing insufficient Cu mass concentration to form Cu3Sn. On the other hand, in samples subjected to isothermal annealing exhibited IMC growth. In samples subjected to thermomigration, near the cold side the Cu concentration is significantly higher, compared to hot side. Extensive surface hardness testing showed increase in hardness from the hot to cold sides, which indicates vacancy migration and Sn grain coarsening are in the opposing direction